How Zn can impede Cu detoxification by chelating agents in Alzheimer's disease: a proof-of-concept study. Issue 39 (19th September 2016) - Conte-Daban, Amandine; Day, Adam; Faller, Peter; Hureau, Christelle
Abstract : Because zinc ions are co-localized with copper ions in the synaptic cleft, they can prevent Cu removal from the amyloid-β peptide and the resulting Cu detoxification by a chelator, unless it has a copper over zinc selectivity higher than the amyloid-β peptide. Abstract : The role of Cu and Zn ions in Alzheimer's disease is linked to the consequences of their coordination to the amyloid-β (Aβ) peptide, i.e. to the modulation of Aβ aggregation and to the production of Reactive Oxygen Species (ROS), two central events of the so-called amyloid cascade. The role of both ions in Aβ aggregation is still controversial. Conversely the higher toxicity of the redox competent Cu ions (compared to the redox inert Zn ions) in ROS production is acknowledged. Thus the Cu ions can be considered as the main therapeutic target. Because Zn ions are present in higher quantity than Cu ions in the synaptic cleft, they can prevent detoxification of Cu by chelators unless they have an unusually high Cu over Zn selectivity. We describe a proof-of-concept study where the role of Zn on the metal swap reaction between two prototypical ligands and the Cu(Aβ) species has been investigated by several complementary spectroscopic techniques (UV-Vis, EPR and XANES). The first ligand has a higher Cu over Zn selectivity relative to the one of Aβ peptide while the second one exhibits a classical Cu over Zn selectivity. How Zn impacts the effect of the ligands on Cu-induced ROS production and Aβ aggregation is also reported.